PERAN ULUMUL QUR'AN DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Anggela, Bella (Institut PTIQ Jakarta, 2024)
Ulumul Qur'an, as a scientific discipline that studies in-depth aspects of the Qur'an, has a very important role in developing the Islamic education curriculum. In an educational context, a deep understanding of the Ulumul Qur'an can help educators and students understand the meaning, context and application of the teachings of the Qur'an in everyday life. This journal will discuss the role of Ulumul Qur'an in the development of the Islamic education curriculum through several sub-chapters which include: Definition and Scope of Ulumul Qur'an, Significance of Ulumul Qur'an in Islamic Education, Implementation of Ulumul Qur'an in the Curriculum, Challenges in Integrating the Ulumul Qur'an, and Recommendations for Curriculum Development. By referring to relevant data and case examples, it is hoped that this journal can provide in-depth insight into the importance of the Ulumul Qur'an in Islamic Education.